Analisis Kesulitan Siswa Dalam Menyelesaikan Soal-Soal Volume Bangun Ruang Sisi Lengkung Pada Siswa Kelas Ix Smp Muhammadiyah 9 Ngemplak Tahun Ajaran 2015/2016 - Yulfiana, Yulfiana (2016)
The aim of this study is to diagnose the learning difficulties and causes difficulities by students in solving problems with volume of curve side. This research is a qualitative descriptive study. The Subject of research study is composed of 25 student of SMP Muhammadiyah 9 Ngempak Class IX B. The technique of collecting the data is observation, test, interview, and documentation. Data analysis techniques through four grooves of data collection, data reduction, data presentation, and conclusion.The results showed that 16 % of students difficulties in applying the concept classified as very low,48,8 % of students difficulties in calculation classified as quite,and 37% of students difficulties applied in problem solving of word math classified as low.Students difficulties causes by external factors:the teachers used teaching methode is not appropriate, the teacher was not provide that vary practice questions, and the teacher is less clear in explaining he concept of curved geometry in the class.